Nostalgisk erindring og polar karrierehistorie. Fridtjof Nansen: Blant sel og bjørn: min første ishavs-ferd (1924) - Karlsen, Silje Solheim (Nordlit, 2012)
In Fridtjof Nansens Hunting & adventure in the Arctic (1924), the last polar travel account Nansen wrote, he writes about his first experience with the Arctic; when he as a young student in 1882 joined the sealboat Viking to the sealing grounds outsideGreenland. The account is a polyphonic book where both the young student and the 63 year old scientist and polar hero alternately speaks. The young Nansen seems overwhelmed by the Arctic surroundings, he tells enthusiastically of ice, polar bears, hunting and the sealing. The old scientist explains the nature and whole fauna in the Arctic, supported by his own experiences and all research available. The result is, on the one hand, a nostalgic travelbook which also functions as a memoir over the totalof Nansen´s Arctic travels and expeditions. On the other hand, the convincing andthorough scientific material in the book positions Nansen as an authority both what regards science, but perhaps just as important: as a successful polar explorer and hero.
Keywords: Fridtjof Nansen; selvframstilling; karrierehistorie; vitenskapsmann; polarhelt.